Development of a Character Education-based Curriculum for Islamic Religious Education at the Junior Secondary School Level - Tika Nurul Hidayati; Cindi Kloudia; Edo Arma Yoga (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Character education has become a critical priority in contemporary education, particularly within Islamic Religious Education at the junior secondary school level, which plays a strategic role in shaping students’ moral and spiritual development. However, the integration of character values into the curriculum remains limited and often unsystematic. Objective: This study aims to analyse the development of a character education-based curriculum for Islamic Religious Education at the junior secondary school level within the framework of the school-based Curriculum. Method: This research employs a qualitative approach, using a library research design, to examine relevant literature on character education, Islamic Religious Education, and curriculum development. Data were analysed through critical review and conceptual synthesis. Results: The findings indicate that an effective curriculum integrates character values such as honesty, responsibility, discipline, and empathy into learning objectives, content, instructional strategies, and assessment practices. Contextual and value-based learning approaches support meaningful internalisation of these values. Conclusion: A systematically designed curriculum can strengthen both religious understanding and character formation in a balanced manner. Contribution: This study provides a conceptual framework for developing a more holistic Islamic Religious Education curriculum that integrates character education comprehensively.